A one-step hot-embossing process for fabricating a channel with superhydrophobic inner walls. (December 2018) - He, Junfeng; Wu, Ming; Zhang, Ruilin; Liu, Jiangwen; Deng, Yu; Guo, Zhongning
Abstract: To produce microfluidic chips cheaply, efficiently, and by mass production, a "one-step" method is proposed herein for fabricating a chip channel and its superhydrophobic inner walls. The flake bulge and micro-pit structure were prepared by chemically etching an S45C steel mold. The influences of etching-solution concentration and etching time on the formation of the hydrophobic structure were studied. A superhydrophobic mold was obtained with a surface contact angle of 156.29° and a sliding angle of 4°. The channel and its inner walls were then duplicated by hot embossing with a poly (methyl methacrylate) substrate. The influences of temperature, pressure, and pressure-holding time on the reproduction accuracy of the superhydrophobic structure were investigated. Stable chip replication was obtained with the following optimal combination of process parameters: a temperature of 145°C, a pressure of 0.8 MPa, and a pressure-holding time of 120 s. The average duplication accuracy achieved was 99.29%, the average surface contact angle was 151.37°, and the average surface sliding angle was 9.3°. The bottom and inner walls of the channel were both observed to be hydrophobic.